378 Injuries among youth mountain bike racing coaches: first year data from a nation-wide injury surveillance system in the United States. (3rd March 2020) - Ehn, Meredith; Cushman, Daniel M; Teramoto, Masaru; Spencer, Chris; Willick, Stuart
Abstract : Background: Youth mountain bike racing is a rapidly growing sport in the United States. An injury surveillance system (ISS) was implemented through a collaboration between University of Utah researchers and the National Interscholastic Cycling Association (NICA) to better understand the characteristics of injuries in this sport and pursue data-driven injury prevention strategies. Objective: Describe the types of and factors associated with injuries sustained by coaches during NICA-sanctioned mountain bike training. Design: A longitudinal ISS was developed using a web-based system. Data were collected from NICA leagues during the 2018 racing season. Designated injury reporters from each team received a weekly email with a link to an injury report form. Coach injury data were reported concurrently with student-athlete injury data. Setting: Nation-wide youth mountain biking leagues in the United States. Participants: 8, 739 coaches participated in the 2018 season, the inaugural year of the NICA ISS. Assessment of risk factors: Variables analyzed included injury characteristics, coach demographics, and factors associated with injuries. Main outcome measurements: Summary measures (frequency and proportion) of injuries and associated factors. Results: A total of 138 injuries from 68 injury events were reported by coaches. The most common injury location and type were shoulder (38.2%) and concussion (17.6%), respectively. 60.3% of all coaches' injuries occurred on downhills. Males and females reported similar injury rates (0.87% and 0.76%, respectively), while injury characteristics differed between sexes, with females sustaining more lower limb injuries. 58.8% of injured coaches sought care in an emergency department. 13.2% of injury events resulted in hospital admission. 43.3% of injury events resulted in time loss of 4 weeks or greater. Conclusions: Interscholastic mountain bike racing is a rapidly growing sport. Acute traumatic injuries are common, not only in athletes but in coaches as well. Dissimilarly to student-athletes, coaches sustained upper extremity injuries more often than concussions. To our knowledge, this is the first ISS to track injuries in coaches.